Analisis Motivasi Kerja Dalam Meningkatkan Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Pegawai - EKA RAMADHANI, FERRA; ROSADIANA, ALFIRA (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
Purpose – To gain new knowledge or make discoveries. As proof or testing of the truth of existing knowledge. As a development of knowledge in an existing scientific field. The objectives that researchers wish to express in conducting this research are as follows: 1) find out the effect of work motivation on employee performance. 2) Knowing the influence of work motivation on job satisfaction and its impact on employee performance.   Design/methodology/approach – Using a quantitative approach, researchers conducted research at the Regional Public Drinking Water Company (PDAM) Among Tirto, Batu City, located on Jl. Kartini No. 10, Stone.The results of the analysis using SPSS 17.0 tools.   Findings – Work motivation influences employee performance and job satisfaction can mediate the influence of work motivation on employee performance. To improve employee performance, it is necessary to be aware of the obligations given. Therefore, researchers suggest to the Regional Public Company for Drinking Water Among Tirto, Batu City, to guide employees to be more responsible for the responsibilities given.   Research limitations/implications – To increase work motivation, it is necessary to pay attention to physiological needs, namely providing a decent salary. Therefore, researchers suggest to the Regional Public Company for Drinking Water Among Tirto, Batu City, to provide decent salaries so that employees feel satisfied so that they can improve employee performance.   Originality/value – To enhance job satisfaction, it is crucial to focus on salary satisfaction, specifically by offering fair salaries. Therefore, researchers suggest to the Regional Public Company for Drinking Water, Among Tirto, Batu City, to provide a fair salary so as not to cause feelings of envy with other employees, so that they feel satisfied at work and can improve employee performance.